2020
DOI: 10.1021/acschemneuro.0c00456
|View full text |Cite
|
Sign up to set email alerts
|

Novel Highly Potent and Selective Sigma1 Receptor Antagonists Effectively Block the Binge Eating Episode in Female Rats

Abstract: In this paper the benzo-cracking approach was applied to the potent sigma1 (σ1) receptor antagonist 1 to afford the less conformationally constrained 1,3-dioxane derivatives 2 and 3. To evaluate the effect of the increase of the distance between the two hydrophobic structural elements that flank the basic function, the cis and trans diastereomers of 4 and 5 were also prepared and studied. Compounds 2 and 3 showed affinity values at σ1 receptor significantly higher than that of the lead compound 1. In particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…On day 68, 24 h after the last administration of PF‐3845, animals were subjected to elevated plus maze (EPM) paradigm, as described in previous studies (Filaferro et al, 2014; Rodi et al, 2008) and the day after (first day without treatment) animals underwent open field test (OFT), as described in Cifani, Micioni Di Bonaventura, et al (2020), Micioni Di Bonaventura et al (2012, 2020). Detailed descriptions of the behavioral tests can be found in Supporting Information Material S1.2.…”
Section: Methodsmentioning
confidence: 99%
“…On day 68, 24 h after the last administration of PF‐3845, animals were subjected to elevated plus maze (EPM) paradigm, as described in previous studies (Filaferro et al, 2014; Rodi et al, 2008) and the day after (first day without treatment) animals underwent open field test (OFT), as described in Cifani, Micioni Di Bonaventura, et al (2020), Micioni Di Bonaventura et al (2012, 2020). Detailed descriptions of the behavioral tests can be found in Supporting Information Material S1.2.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the BE model is reported in Supplementary Materials . In accordance with the higher prevalence of eating disorders among young adolescents and adult women rather than men, female rats were used [ 6 , 79 ], as in previously published works [ 80 , 81 , 82 ].…”
Section: Methodsmentioning
confidence: 99%
“…With no BED phenotype, the result demonstrates only an effect to decrease hyperphagia, not efficacy against the psychopathology of BED. Cifani et al (2020) have recently reported that sigma-1 antagonists show potential as drugs to treat BED. This result requires further replication because the fasting/stress BED model is claimed to have predictive validity partly based on the differential actions of sibutramine and topiramate (Cifani et al, 2009).…”
Section: Research Directions Into New Drugs To Treat Binge-eating Dis...mentioning
confidence: 99%